Analisis Kecenderungan Gaya Belajar Mahasiswa Pendidikan Agama Kristen Semester IV Institut Agama Kristen Negeri Kupang Tahun 2022 - Bole, Moses Yohanis Nimrot; Foeh, Yonatan; Radja, Petrus Logo (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
As prospective teachers, Christian religious education students must be able to recognize their own learning styles so that when they become teachers, they can know and recognize the learning styles of their students. In this way he can determine the appropriate strategy or method for delivering learning to students. Based on the background above, the aim of this research is to find out the learning styles of 4th semester Christian religious education student at the Kupang State Christian Religion Institute and to understand the factors that hinder Christian religious education students from not knowing and recognizing their learning styles. The research method used in this research is quantitative descriptive research. The data collection technique uses a questionnaire. The number of samples in this study was 62 people. The data analysis technique used is descriptive statistics. The results of research conducted on 4th semester Christian religious education student at the Kupang State Christian Religion Institute, concluded that there was a tendency for student learning styles, namely visual kinesthetic (43.5%). There are also factors that hinder students in knowing and applying their learning styles, namely feeling bored or bored and stressed in the learning process, physical conditions such as visual and hearing problems, obstacles when lecturers deliver material in the learning process, and the absence of special time provided for studying.